PENGEMBANGAN MODUL AJAR BERBASIS PMRI MENGGUNAKAN KONTEKS PASAR INPRES LUBUKLINGGAU PADA MATERI ARITMATIKA SOSIAL KELAS VII - Selviyani, Anggi; Refianti, Rani; Purwasi, Lucy Asri (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
This study aims to produce PMRI-based teaching modules using the market context of Inpres Lubuklinggau on class VII social aritamtics material that is valid, practical, and has potential effects. This research is a development research using the ADDIE development model, which consists of stages: analysis, design, development, implementation and evaluation. Data collection techniques were carried out through interviews, observations, questionnaires, and tests, with the subjects of the study being grade VII students of SMPIT Mutiara Cendekia Lubuklinggau totaling 6 students for the small group test and 24 students for the field test. Based on the results of data analysis, it shows that Aiken's V value from the validation of linguists is 0.85, media experts are 0.83 and material experts are 0.81 with very valid categories. In the practicality test, teachers and students obtained an overall percentage of 85.34% in the very practical category. And the results of the potential effect test through tests given by 24 students obtained data that 21 students (88%) were included in the complete category and 3 students (12%) with the incomplete category.